Keanekaragaman Jenis Burung di Kawasan Perkotaan Perwakilan Lima Pulau Besar di Indonesia: Kajian Literatur - Amanda Ayupuspita; Cut Putroe Safira Annika; Fuad Syawal Ryanda; Dinda Arisandi; Ana Maria; Hijratul Abdi; Aida Fithri; Widya Sari (Jurnal Bioleuser, 2024)
Birds play a vital role in ecosystems, such as aiding in flower pollination and seed dispersal. In urban areas, their presence largely depends on the availability of safe and supportive habitats. One key element is urban forests, which are part of Green Open Spaces (RTH) and serve to maintain the ecological functions of birds in urban environments. However, research on birds in urban areas of Indonesia remains limited, with existing data covering only a small number of cities and regions. This study aims to identify the diversity of bird species in urban areas representing the five major islands of Indonesia (Sumatra, Java, Kalimantan, Sulawesi and Papua) through a literature review. Data were gathered from various sources related to bird species in major cities and analyzed using the Shannon-Wiener diversity index. The findings revealed the presence of 142 bird species distributed across 14 orders in Indonesia's urban areas. The bird diversity index reached a high value of 4.7. These results highlight the significant diversity of bird species in Indonesian urban environments and underscore the importance of conserving bird habitats in urban areas to support the sustainability of urban ecosystems.